On the predictability of magnetic field inversion within a simple dynamic model - Frick, P.G.; Pleshkov, R.A. (Perm Federal Research Centre Journal, 2025)
A viscous generalization of the Rikitake two-disk dynamo model, known as the simplest dynamic model of random reversals of the geomagnetic field, is considered. A systematic study of the emerging solution modes in the parameter space (the degree of ohmic dissipation and the ratio of the moments of forces rotating the disks) has been carried out under a fixed magnetic Prandtl number Pm=10-6, acceptable for the liquid core of the Earth. It is shown that there is a narrow domain in the parameter space in which the rare-reversal chaos, characterized by very long chrones (time intervals during which the sign of the magnetic field is preserved), within which the solution is quasi-stable, and the field fluctuations are characterized by a small amplitude and an extremely slow growth rate. Some regularity of the evolution of field disturbances within a single chron has been revealed, which makes it possible to predict the time of the next magnetic field reversal.